Pengaruh Besi (Fe) dan Bahan Organik Terhadap Perilaku Pertukaran Amonium pada Tanah Ultisol Natar - Tio Ramdoni; Jamalam Lumbanraja; Supriatin; Sarno (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2021)
The low availability of ammonium (NH4+) in Ultisols due to the high Fe ion content can be overcome by adding organic matter. The Quantity-Intensity (Q / I) method was used to study the behavior of NH4+ exchange in the soil. The purpose of this study was to study the exchange behavior of NH4+ (CRNH40, PBCNH4+, ?NH40, KG) due to the addition of Fe and organic matter to Ultisol soil. This research was conducted at the Laboratory of Soil Science, Faculty of Agriculture, University of Lampung. The treatment applied consisted of 5 treatments: (1) Soil = 100% T; (2) Soil + FeCl3 = 98% T + 2% Fe; (3) Soil + FeCl3 + BO = 93% T + 2% Fe + 5% BO; (4) Soil + Concretion = 80% T + 20% K; (5) Soil + Concretion + BO = 75% T + 20% K + 5% BO. While the series solution used is made of NH4Cl 100 mmol L-1 and CaCl2 1000 mmol L-1 consisting of T1 = 0 mmol L-1 NH4Cl + 5 mmol L-1 CaCl2, T2 = 0.5 mmol L-1 NH4Cl + 5 mmol L-1 CaCl2, T3 = 1.0 mmol L-1 NH4Cl + 5 mmol L-1 CaCl2, T4 = 1.5 mmol L-1 NH4Cl + 5 mmol L-1 CaCl2, T5 = 2.0 mmol L -1 NH4Cl + 5 mmol L-1 CaCl2, and T6 = 3.0 mmol L-1 NH4Cl + 5 mmol L-1 CaCl2. Data were tested by Student-t test at the real level of 5%. The results of this study indicate that: (1) the addition of Fe to Ultisol soil significantly reduces the buffering capacity of ammonium (PBCNH4+), NH4+ equilibrium (?NH40), Gapon coefficient (KG), and increases the concentration ratio (CRNH40). (2) Giving iron concretion to Ultisol soil has a significant effect on reducing the Potential Buffering Capacity of ammonium (PBCNH4+), Gapon Coefficient (KG) and increasing the Concentration Ratio (CRNH40), but it does not significantly reduce NH4 + equilibrium (?NH40). (3) Organic matter given to Ultisol soil increases the Potential Buffering Capacity of ammonium (PBCNH4+), NH4+ equilibrium (?NH40), and Gapon Coefficient (KG), but the Concentration Ratio (CRNH40) also increases in Ultisol Natar Soils.